Pendekatan Saintifik untuk Meningkatkan Kemampuan Kognitif Siswa pada Sifat Koligatif Larutan Elektrolit - Mu'minah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2022)
The low cognitive abilities of students learning chemistry in class XII MIPA 3 MAN 1 Ciamis motivated this study. The research objective was to find out the scientific approach to improving students' cognitive abilities and its impact on the colliding properties of electrolyte solutions in class XII MIPA 3 MAN 1 Ciamis in the 2019/2020 academic year. The method used in this research is classroom action research (CAR), which consists of two cycles, each going through stages: planning, implementing action, observing, and reflecting. The results showed that the teacher's ability to use a scientific approach in cycle I obtained a score of 35, or 79.55%; in cycle II, a score of 43, or 97.73%, compared to an ideal score of 44. Students' ability in pre-cycle obtained an average score of 77 out of 54. Then it increased in cycle I with a score of 84.38, and in cycle II, it increased to 89.81 from an ideal score of 100. The impact of the scientific approach on students' cognitive abilities in relation to the collative properties of electrolyte solutions in class XII MIPA 3 MAN 1 Ciamis includes the results of observations of students' cognitive abilities. In the collative properties of the electrolyte solution in PBM in Cycle II, an average score of 89.62 was obtained. From the learning outcomes in Cycle II, 14 students scored 90–100 (53.85%), and 12 students scored between 80–90 (46.15%).